Osteoclastic Giant Cell Rich Squamous Cell Carcinoma of the Uterine Cervix: A Case Report and Review of the Literature - Lucía Alemán-Meza; Gabriela Sofía Gómez-Macías; Oralia Barboza-Quintana; Raquel Garza-Guajardo; Abelardo Loya-Solis (Case Reports in Pathology)
Cervical carcinoma is the most common malignancy of the female genital tract and represents the second most common malignancy in women worldwide. Histologically 85 to 90% of cervical cancers are squamous cell carcinoma. Osteoclastic giant cell rich squamous cell carcinoma is an unusual histological variant of which only 4 cases have been reported. We present the case of a 49-year-old woman with a 6-month history of irregular vaginal bleeding. Examination revealed a 2.7 cm polypoid mass in the anterior lip of the uterine cervix. The patient underwent hysterectomy with bilateral salpingo-oophorectomy. Microscopically the tumor was composed of infiltrative nests of poorly differentiated nonkeratinizing squamous cell carcinoma. Interspersed in between these tumor cells were numerous osteoclastic giant cells with abundant eosinophilic cytoplasm devoid of nuclear atypia, hyperchromatism, or mitotic activity. Immunohistochemistry was performed; CK and P63 were strongly positive in the squamous component and negative in the osteoclastic giant cells, while CD68 and Vimentin were strongly positive in the giant cell population and negative in the squamous component. The patient received chemo- and radiotherapy for recurrent disease identified 3 months later on a follow-up CT scan; 7 months after the surgical procedure the patient is clinically and radiologically disease-free.